Intravenous DSA and dynamic computed tomography for postoperative follow-up of type A aortic dissections - Hendrickx, Philippe; Rieder, P.; Prokop, Mathias; Milbradt, H.; Karck, Matthias; Laas, Joachim (European journal of radiology, 1989)
We undertook a direct comparison of intravenous digital subtraction angiography and dynamic computed tomography in a follow-up study on 37 patients who had undergone surgery on the thoracic aorta for acute or chronic type A dissections. These are minimally invasive and complementary procedures: IV-DSA provides a clear angiographic image of the dissection, with visualization of the true and false channels, their distal extension and the supra-aortic and abdominal vessels they supply. Dynamic CT best demonstrates the proximal extension of the disease; it visualizes clotting in the false lumen and permits a more accurate measurement of the aortic width, and thus early recognition of a developing aneurysm.